Making America safe again: public support for policies to reduce terrorism - Haner, Murat (Deviant behavior, 2021)
A number of homeland security measures have been implemented or proposed since the terrorist attacks of September 11, 2001. While public opinion polls suggest that some of these measures (e.g., universal security checks) have received widespread support, security policies advanced by President Donald Trump that target Muslims and other immigrant groups are more controversial. These polices have conflated immigration with terrorism and have generated anti-immigrant sentiment in some segments of the American public. In this paper, we utilize national survey data to examine the social sources of public support for national security measures, with a focus on policies that emphasize border control, universal security, reduced civil liberties, discriminatory surveillance, and exclusion. We also determine the extent to which support for policies specific to the Trump administration is driven by Trump’s voter base - White, male, older, southern, Christian, and conservative and assess the influence of anti-immigrant attitudes. Our analyses reveal that the American public favors security measures that are applied universally, and characteristics of Trump’s voter base further predict policy support. Our findings also suggest that support of discriminatory security policies is largely explained by the perception that immigrants are dangerous. We discuss the implications of the anti-immigrant and anti-Muslim rhetoric that has stemmed from Trump’s presidential campaign and subsequent administration for national security policies.